Pengembangan Bahan Ajar PAI Berbasis Nilai-nilai Aulawiyah dalam Pemahaman Islam Wasathiyah di SMA Madinatul Ulum Tembelang - Arrosyid, Mokhammad Iqbal; Zulfah, Machnunah Ani (ISLAMIKA, 2024)
Radicalism is an ideology that uses violence in its actions. The spread of radicalism is a serious problem for a nation, the main target of its spread is through educational institutions as has happened. So efforts are needed to instill Wasathiyah Islam or moderation as a way to prevent the entry of radicalism. This research aims to develop teaching materials for Islamic Religious Education (PAI) based on Aulawiyah values and understanding Wasathiyah Islam in class 1 of Madinatul Ulum Tembelang Jombang High School. This development research uses the ADDIE development model. Data collection techniques use observation, questionnaires, pretest and posttest. The implementation of the book developed was considered quite effective based on the results of the pretest and posttest with a percentage result of 55.44%. With the teaching materials developed, it is hoped that it can provide knowledge in preventing the spread of radicalism and a source of reference for teaching materials about Moderation.